2006
DOI: 10.1242/jcs.02856
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lectins: the calnexin/calreticulin chaperone system of the endoplasmic reticulum

Abstract: The structure of the ER-luminal portion of Cnx, solved by Xray crystallography (Schrag et al., 2001), reveals two domains: a globular ␤-sandwich domain that resembles legume lectins; and an extended 140 Å arm domain consisting of two ␤-strands folded in a hairpin configuration ( Fig. 2A). Each ␤-strand is composed of four tandemly repeated, proline-rich repeats, which is why the extended arm is frequently referred to as the P domain. For Crt, only the arm domain structure has been solved by NMR methods. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
368
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(376 citation statements)
references
References 102 publications
8
368
0
Order By: Relevance
“…These N-glycans are recognized by ER lectin-like chaperones calnexin (CNX) and/ or calreticulin (CRT), which promote proper folding by preventing aggregation and premature export from the ER (Fig. 1C) (Williams 2006;. Trimming of the innermost glucose residue by glucosidase II releases those polypeptides from CNX/CRT.…”
Section: Protein Folding and Posttranslational Modification Glycosylamentioning
confidence: 99%
“…These N-glycans are recognized by ER lectin-like chaperones calnexin (CNX) and/ or calreticulin (CRT), which promote proper folding by preventing aggregation and premature export from the ER (Fig. 1C) (Williams 2006;. Trimming of the innermost glucose residue by glucosidase II releases those polypeptides from CNX/CRT.…”
Section: Protein Folding and Posttranslational Modification Glycosylamentioning
confidence: 99%
“…We also observed aberrant intracellular localization of the expressed hGGT2 proteins. These data indicate that the glycosylated hGGT2 propeptides likely fail to fold properly and arrest in the ER where they are shepherded by resident chaperones for targeted degradation (31,54). The only evidence that hGGT2 transcripts are actively translated in vivo is a report in which a single tryptic peptide unique to the amino-acid sequence of hGGT2 was identified during a high-throughput mass spectrometric characterization of human liver glycopeptides (7).…”
Section: Discussionmentioning
confidence: 99%
“…28 The aequorin-based measurement, applied in our study, is based on a protocol which includes (i) pre-incubation of cells with the aequorin cofactor coelenterazine n, following complete Ca 2 þ depletion of the ER in Ca 2 þ -free medium; (ii) refilling of the ER by addition of 1 mM CaCl 2 to the extracellular medium until [Ca 2 þ ] in the ER lumen ([Ca 2 þ ] ER ) reaches steady state; and (iii) release of Ca 2 þ through Ca 2 þ leak or release channels 29,30 (see also Materials and Methods). The strategic advantage of this protocol was that it allowed us to analyze separately the three fundamental parameters of ER Ca 2 þ homeostasis, respectively: (i) Ca 2 þ accumulation into the ER, through the complex interplay between store-operated Ca 2 þ influx into the cell immediately followed by its transport into the ER lumen by sarcoendoplasmic reticulum Ca 2 þ -ATPase (SERCA); 31,32 (ii) steadystate ER luminal Ca 2 þ concentration ([Ca 2 þ ] ER ) determining Ca 2 þ -dependent folding and redox processes of the organelle 33,34 ; and (iii) the Ca 2 þ leak observed after inhibition of SERCA-mediated Ca 2 þ uptake by 2,5-di(t-butyl)-1,4-benzohydroquinone (tBHQ) 29 (Figure 7). Based on these data, we concluded that Ca 2 þ is a major regulator of CRT translocation.…”
Section: Rtn-1c and Mito Reduce Er Luminal [Camentioning
confidence: 99%